The Dual Effect Of Fear Of Missing Out (FOMO) On Learning Patterns In Students - Adrian Atsil Ghaisana; Arsy Kayyasa Wafi Randan; Gayatri Bhanurasmi Achmad Putri; Jihan Hafidzah Azaria; Arina Haque (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025